2006 IEEE 8th International Conference on Properties and Applications of Dielectric Materials 2006
DOI: 10.1109/icpadm.2006.284108
|View full text |Cite
|
Sign up to set email alerts
|

Promising Characteristics of Nanocomposite Dielectrics

Abstract: Polymer nanocomposites possess promising high performances as engineering materials, if they are prepared and fabricated properly. It was also clarified that they could provide favorable performances as dielectrics and electrical insulation. Comprehensive reviews were given in literatures by the author firstly in 2004 and secondly in 2005. This review is based on the second paper and covers recent significant findings. It also utilizes a recently proposed multi-core model, i.e. a fine structure of "interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The theoretical investigations in this Letter indicate the importance of filler dispersion. It is mathematically shown that the ISA shows exactly similar characteristics as the observed physical phenomena [1–16, 20], supporting the role of ISA in the material properties of nanocomposites.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The theoretical investigations in this Letter indicate the importance of filler dispersion. It is mathematically shown that the ISA shows exactly similar characteristics as the observed physical phenomena [1–16, 20], supporting the role of ISA in the material properties of nanocomposites.…”
Section: Introductionmentioning
confidence: 59%
“…As can be seen from the above Figures, both ISA and interparticle distance tend towards improvement with increasing filler content. However, experimental results indicate that the improvements in material properties tend to saturate with increasing filler content [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]20]. The reason for this may be understood in the light of the fact that the results shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, many studies have been focused on developing new materials with superior strength and attributes. Among these, the development of materials using the concept of composite materials has long been of much interest [1].…”
Section: Introductionmentioning
confidence: 99%